Combination of Capped Gold Nanoslit Array and Electrochemistry for Sensitive Aqueous Mercuric Ions Detection - Cheng-Chuan Chen; Shu-Cheng Lo; Pei-Kuen Wei (Nanomaterials, 2021)
Label-free surface plasmon resonance (SPR) detection of mercuric ions in various aqueous solutions, using capped gold nanoslit arrays combined with electrochemical (EC) sensing technique, is demonstrated. The nanoslit arrays are fabricated on flexible cyclo-olefin polymer substrates by a nanoimprinting lithography method. The EC and SPR signals for the investigation of current responses and transmission SPR spectra are simultaneously measured during metal ions electrodeposition. Glycerol–water solution is studied to evaluate the resonant peak wavelength sensitivity (480.3 nm RIU−1) with a FOM of 40.0 RIU−1 and the obtained intensity sensitivity is 1819.9%. The ferrocyanide/ferricyanide redox couple performs the diffusion controlled electrochemical processes (R2 = 0.99). By investigating the SPR intensity changes and wavelength shifts of various mercuric ion concentrations, the optical properties are evaluated under chronoamperometric conditions. The sensors are evaluated in the detection range between 100 μM and 10 nM with a detection limit of 1 μM. The time dependence of SPR signals and the selectivity of 10 μM Hg2+ in the presence of 10 μM interfering metal ion species from Ca2+, Co2+, Ni2+, Na+, Cu2+, Pb2 + and Mn2+ are determined. The capped gold nanoslit arrays show the selectivity of Hg2+ and the EC sensing method is effectively utilized to aqueous Hg2+ detection. This study provides a label-free detection technique of mercuric ions and this developed system is potentially applicable to detecting chemicals and biomolecules.